Accompaniment the Successful Strategies Based on Research of Customer Loyalty - Khairil Anwar; Retno Dewanti; Tjia Fie Chu (Bina Nusantara University, 2019)
This study aims to find out the effect of brand awareness and customer satisfaction on corporate image and its impact on customer loyalty in laurier products of PT Kao Indonesia. Customer Loyalty is one of the core goals pursued in modern marketing. By loyalty, it is expected that corporates will get long-term profitability. This study uses quantitative approach and involves 52 respondents in kelurahan Cikoko as the samples collected using probability sampling and simple random sampling techniques. Data processing employs SPSS 24 and the results of the study show that brand awareness, customer satisfaction and corporate image has significant influence on customer loyalty; therefore, the proposed program assistance is necessary to be the strategy in determining the success of customer loyalty of Laurier product.